KONSEP HARTA SEUHAREKAT (Suatu Kajian Normatif Antara Hukum Islam dan Undang-undang) - Ahmad Yani; Safriadi (Fakultas Syariah Institut Agama Islam Negeri Lhokseumawe, 2019)
This study raised about The Concept Of Seuharekat (A Normative StudyBetween Islamic Law and Living Laws). In this study, the authors usethe research library (library research), and data collection is done byreviewing books and books of fiqh as well as the laws and regulationsin force in Indonesia as a primary ingredient, and other books relatedto the discussion of this research as a material secondary, so thispattern qualitative form. In addition, analysis by the writer isdescriptive analysis. From the results of this study concluded that theformulation of the treasure found together in marriage law inIndonesia is one manifestation of a new formulation of the legalcharacter of Indonesia. Institutionalization allegedly as a reflectionresponsive to the laws of life in the midst of Indonesian society (al-Adat al-Muhakkamat). The formulation of joint property in fiqh can beknown through analogy into shirkah Amlak. This is based on severalreasons, the first is that no form through contract. Secondly when thereis a desire to share the treasure union, then divided equally betweenthe unionized. In addition, the lack of capital in the incorporation ofthe property will be divided. According to the Indonesian marriagelaw, that property generated during the marriage become the jointproperty of husband and wife. Marriage law also does not provide aconcrete explanation of the division of joint property if the marriagebroke up, either because of divorce divorce, contested divorce or onedies. In the case of marriages break up because divorce is onlydetermined that the joint property is set according to its own laws.While the definition of the respective legal explanation is that thereligious law, customary laws, and other laws. This means that anyapplicable law is in accordance with the agreement of the partiesconcerned. It is given that in Indonesia there are various family systemaffects the joint property ownership